Relationships between mitochondrial content and bioenergetics with obesity, body composition and fat distribution in healthy older adults. Issue 1 (December 2015) - Bharadwaj, Manish; Tyrrell, Daniel; Leng, Iris; Demons, Jamehl; Lyles, Mary; Carr, J.; Nicklas, Barbara; Molina, Anthony
Abstract Background Mitochondrial function declines with age; however, the relationship between adiposity and mitochondrial function among older adults is unclear. This study examined relationships between skeletal muscle mitochondrial content and electron transport chain complex 2 driven respiration with whole body and thigh composition, body fat distribution, and insulin sensitivity in older adults. Methods 25 healthy, sedentary, weight-stable men (N = 13) and women (N = 12) >65 years of age, with a BMI range of 18-35 kg/m2, participated in this study. Vastus lateralis biopsies were analyzed for citrate synthase (CS) activity and succinate mediated respiration of isolated mitochondria. Whole body and thigh composition were measured by DXA and CT. HOMA-IR was calculated using fasting glucose and insulin as an estimate of insulin sensitivity. Results Similar to reports in middle-aged adults, skeletal muscle CS activity was negatively correlated with BMI (R = −0.43) in our cohort of older adults. Higher total and thigh adiposity were correlated with lower CS activity independent of BMI (R = −0.50 and −0.71 respectively). Maximal complex 2 driven mitochondrial respiration was negatively correlated with lower body adiposity in males (R = −0.66). In this cohort of non-diabetic older adults, both HOMA-IR and insulin were positively correlated with CS activity when controlling for BMI (R = 0.57 and 0.66 respectively). Conclusions Adiposity and body composition are correlated with skeletal muscle mitochondrial content and electron transport chain function in healthy, sedentary, community dwelling, older adults. Specific relationships of mitochondrial bioenergetics with gender and insulin sensitivity are also apparent. Trial registration ClinicalTrials.gov identifierNCT01049698